Development of a Modified Psoriatic Arthritis Disease Activity Score Using the Medical Outcomes Study Short Form 12 as a Measure of Quality of Life. Issue 4 (12th March 2020) - Perruccio, Anthony V.; Got, Matthew; Li, Suzanne; Ye, Yang; Gladman, Dafna D.; Chandran, Vinod
Abstract : Objective: The Psoriatic Arthritis Disease Activity Score (PASDAS) is a composite measure of psoriatic arthritis (PsA) disease activity. The length of its patient‐reported components raises concern about questionnaire burden. The PASDAS includes the Medical Outcomes Study Short Form 36 (SF‐36) health survey. We undertook this study to investigate the agreement between the PASDAS and a modified PASDAS (mPASDAS), which substituted the SF‐36 with the shortened SF‐12. Methods: A total of 100 patients who fulfilled the criteria of the Classification of Psoriatic Arthritis Study Group for PsA were consecutively recruited. All of the PASDAS‐required variables were collected. The 12 item responses for SF‐12 were extracted from the SF‐36 questionnaire. The PASDAS and the mPASDAS were calculated using the SF‐36 and SF‐12 scores, respectively. A Bland‐Altman plot of the mean differences in PASDAS and mPASDAS scores was generated to evaluate agreement. Construct validity was assessed by examining correlations of the PASDAS and the mPASDAS with the Health Assessment Questionnaire, the Functional Assessment of Chronic Illness Therapy–Fatigue subscale, the EuroQol 5‐domain instrument (health‐related quality of life), and pain scores (range 0–10, visual analog scale). The kappa statistic was used to measure agreement between disease activity states as determined by the PASDAS and mPASDAS. Results: The mean ± SD PASDAS and mPASDAS was 3.29 ± 1.39 and 3.24 ± 1.27, respectively. The correlation between the 2 scores was 0.998 ( P < 0.0001), and the mean difference was –0.05 (95% confidence interval [95% CI] –0.07, –0.03). Construct validity was found, with nearly identical correlations of the PASDAS and mPASDAS with each of the external health measures. The misclassification rate with the mPASDAS was only 6%. The weighted κ = 0.90 (95% CI 0.82, 0.97). Conclusion: The mPASDAS may replace the PASDAS in disease activity assessment given the excellent agreement, validity, and low misclassification rate.